Combining internal and external motivations in multi-actor governance arrangements for biodiversity and ecosystem services. Issue 58 (April 2016) - Dedeurwaerdere, Tom; Admiraal, Jeroen; Beringer, Almut; Bonaiuto, Flavia; Cicero, Lavinia; Fernandez-Wulff, Paula; Hagens, Janneke; Hiedanpää, Juha; Knights, Paul; Molinario, Erica; Melindi-Ghidi, Paolo; Popa, Florin; et al.
Graphical abstract: Highlights: Presents an EU-wide survey of 34 multi-actor biodiversity governance arrangements. Non-economic motivations are compatible with involvement of private companies. Identifies actor self-determination as a key success factor. Inclusive governance contributes to opting in of internally motivated behaviour. Internally motivated behaviour compatible with economic benefits to society. Abstract: This paper analyses the possibility of building a mutually supportive dynamics between internally and externally motivated behaviour for biodiversity conservation and ecosystem services provision. To this purpose a face to face survey amongst 169 key actors of 34 highly successful and prominent biodiversity arrangements in seven EU countries was conducted. The main finding of the paper is the feasibility of combining inherently intrinsically motivated behaviours (providing enjoyment, pleasure from experimentation and learning, aesthetic satisfaction) and internalized extrinsic motivations (related to the identification with the collective goals of conservation policy) through a common set of governance features. Successful initiatives that combine internal and external motivations share the following features: inclusive decision making processes, a broad monitoring by "peers" beyond the core staff of the initiatives, and a context that is supportive for the building of autonomous actor competences. These findings are in line with the psycho-sociological theory of motivation, which shows the importance of a psycho-social context leading to a subjective perception of autonomy and a sense of competence of the actors.